1968
DOI: 10.1143/jjap.7.122
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposition of Silicon Nitride Film on Silicon and Properties of MNS Diodes

Abstract: Silicon nitride film was deposited on silicon by gas phase reaction between SiH4 and NH3 using N2 as the carrier gas and a horizontal resistance-heated furnace at the temperature range of 650 to 950°C. The higher the substrate temperature became, the larger the wave number of the infrared, which corresponds to the maximum absorption. Film deposited at lower temperature always showed the hysteresis of C-V curve, but it almost disappeared by elevating substrate temperature and supplying much amount of ammonia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Either the range where the phosphorus concentration is sufficiently high was too small, the anneal temperatures were too low, or additional oxygen is necessary. We do not believe that the nondetection is caused by the choice of transmission instead of reflectance measurements because this choice was made in accordance with the work of Fraenz et al (7) who found the band very pronounced in transmission.…”
mentioning
confidence: 70%
“…Either the range where the phosphorus concentration is sufficiently high was too small, the anneal temperatures were too low, or additional oxygen is necessary. We do not believe that the nondetection is caused by the choice of transmission instead of reflectance measurements because this choice was made in accordance with the work of Fraenz et al (7) who found the band very pronounced in transmission.…”
mentioning
confidence: 70%
“…Manuscript received Oct. 14, 1971. This was Paper 63 presented at the Cleveland, Ohio, Meeting of the Society, Oct. [3][4][5][6][7] 1971.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…It has very attractive chemical and physical properties which have encouraged its use as a coating material for microelectronic devices. Several methods (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) of preparing silicon nitride have been reported in the literature. The three major methods for depositing silicon nitride on high melting substrates are: (i) chemical vapor deposition, (ii) reactive sputtering, and (iii) rf glow discharge.…”
mentioning
confidence: 99%
“…Silicon nitride (Si x N 4 ) is a material commonly used in microelectronic industry for its strong mechanical resistance and its insulator and chemical barrier properties. Because of its biocompability, Si x N 4 also finds application in biomedical and biosensor fields. In comparison with silicon, it offers the extra advantage of a low optical refractive index, , which is favorable for several detection schemes in the biochip context . Such a material can be easily obtained as thin films by (plasma-enhanced) chemical vapor deposition ((PE)-CVD) or by reactive magnetron sputtering. When exposed to atmosphere, silicon nitride is covered by a native oxynitride layer which needs to be removed for some applications.…”
Section: Introductionmentioning
confidence: 99%